SA – Life Collection
A compilation of short films from 1992 and 1993, shot during the siege of Sarajevo by a group of multi-ethnic film makers from Sarajevo (SAGA). The film includes the following SAGA productions: “Traveling Children,” February 1993, Antonije Nino Žalica; “Eight Years After,” July 1992, Ademir Kenović and Antonije Nino Žalica; “Sa druge strane rijeke” (“On the Other Side of the River”); music video “Help Bosnia Now” performed by the Bosnian Band Aid; “Palio sam noge” (“I Burnt Legs”), June 1992 – March 1993, Srđan Vuletić; “Water and Blood,” January 1993; “War Art,” March 1993, Nedžad Begović; “Confessions of a Monster,” November 1992, Ademir Kenović and Ismet Arnautalić.